How to make z the subject of the formula?

z=(y(z-y))/x

2 Answers
Feb 17, 2018

z=(-y^2)/(x-y)

Explanation:

Expand the expressions and then factor out z:

z=(y(z-y))/x

z=(yz-y^2)/x

zx=yz-y^2

zx-yz=-y^2

z(x-y)=-y^2

z=(-y^2)/(x-y)

Or, if you would like to rearrange the terms:

z=(-1* y^2)/(x-y)

z=-1* (y^2)/(x-y)

z=(y^2)/(-1* (x-y))

z=(y^2)/(-x+y)

z=y^2/(y-x)

Feb 17, 2018

z=-(y^2/{x-y})

Explanation:

Firstly, multiply x and z =xz
Then multiply y(z-y) which equals to yz-y^2
Shift yz to the left, zx-zy=-y^2
Then take out z, z(x-y)=-y^2\
Then divide -y^2 by x-y, z=-(y^2/{x-y})
So, z=-(y^2/{x-y})